Online Education on the Development of Functional Foods and the Nutrients Encapsulation - Lanny Sapei; Natalia Suseno; Hendrik Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The modern society lifestyle triggers a tendency for people to consume fast food with high-calorie, low-nutrient, and low-fiber. Due to the COVID-19 pandemic, society is becoming more aware of maintaining health by consuming healthy and nutritious foods. Therefore, the target of this educational webinar program was educated individuals in the education sector, and they were expected to influence their surrounding communities to adopt healthy eating patterns through the consumption of functional foods. Oil-in-water (O/W) food emulsions such as milk, mayonnaise, and creamer are widely consumed in processed foods. The development of Fiber CrèmeTM creamer as a substitute for milk/coconut milk, which is low sugar, trans-fat-free, and high fiber, has been produced by PT. LNK to enhance the taste of processed foods and beverages. Compounds such as vitamins, minerals, and antioxidants can be encapsulated within the emulsion system, such as using Virgin Coconut Oil (VCO) in creamer products. This webinar was attended by 103 participants, with 80% coming from the education sector. The participants' high level of knowledge and awareness was reflected through online questionnaires and comments. This educational webinar encourages the community to sustainably enhance body immunity by consuming functional foods.